Evaluation of two infants with myotonic dystrophy by the McFie's diagram from the results of WISC - CRISTINA MARIA DUARTE WIGG; LUIZ ANTONIO ALVES DURO (Arquivos de Neuro-Psiquiatria)
In this paper the authors disclose the result of a research carried out on two brothers whose parents were first cousins, being the gene transmitted by the father. The psychological test Wechsler Intelligence Scale of Children (WISC) was used in two occasions in order to assess the verbal and non-verbal skills. FRM and IRM were nine and eleven-year-old respectively, in the first examination, being the former thirteen and the latter fifteen-year-old on the second one. A comparison between the McFie's diagram and the WISC scores was made: the McFie's diagram showed the impairment severity in each cortical lobe when the left hemisphere was compared with the right one. The McFie's diagram was made from WISC's scores: the McFie's diagram showed the impairment severity in each cortical lobe when the left hemisphere was compared with the right one. On the second examination the performance was worse than in the first, mainly in the non-verbal aspects. The IRM's diagram showed a reduction in the right frontal and parietal lobes. In the FRM's diagram a reduction in the left frontal, temporal and parietal lobes, and also, in the right parietal lobe was found. The visual-spatial constructive aspects showed greatest impairment in this result.